Chemical castration and sexual crimes against minors: a legal-constitutional examination from a human rights perspective in Ecuador - Maza Erreiz, Janeth Valeria; Ochoa Merino, Daniela (Revista Universidad de Guayaquil, 2026)
Sexual violence against children and adolescents in Ecuador remains high, with a significant gap between reported cases and convictions. This has prompted proposals for harsher penalties, such as chemical castration for sex offenders. The objective of this study was to analyze the legal and ethical feasibility and the effectiveness of implementing chemical castration as an additional measure for sexual offenses against minors within the framework of a constitutional state of rights and justice. A qualitative and documentary literature review was conducted, following PRISMA guidelines adapted to socio-legal studies. Articles were searched in academic and publishing databases indexed in recent years, applying predefined inclusion and exclusion criteria, and a review matrix was constructed that systematized clinical, bioethical, and penal findings. The results show that, although hormone therapy temporarily reduces sexual desire, the available evidence on its effect on reducing recidivism is limited and is associated with significant adverse physical and psychological effects. From a legal standpoint, mandatory chemical castration conflicts with dignity, personal integrity, bodily autonomy, and the resocializing purpose of punishment. It is concluded that chemical castration does not constitute an adequate penological response compatible with human rights in Ecuador and that public policies should be geared towards strengthening criminal investigations, providing comprehensive protection for victims, and structurally preventing sexual violence.